Thalassoporum longitrichum sp. nov., a marine epizoic cyanobacterium with anti-inflammatory potential, and the taxonomic reassessment of Limnothrix Meffert - C. Tenorio Rodas; G.S. Hentschke; F. Oliveira; G. Lopes; A. Duarte; J. Morone; A. Campos; V. Vasconcelos (Algal Research, 2026)

Mainstream and fast-track genetic testing in pancreatic cancer patients and its impact on treatment: our experience in a tertiary hospital in Spain - M. Bringas; I. Echavarría; C. Polo; N. Jiménez-Alduán; C. Flores; A. Muñoz; L. Ortega; G. Torres; J. Soto-Alsar; A. Calvo; P. García Alfonso; J. A. Pajares; et al. (Familial Cancer, 2026)

Modeling MBR fouling: A critical review analysis towards establishing a framework for good modeling practices - V. Sandoval-García; M.V. Ruano; M. Alliet; C. Brepols; J. Comas; J. Harmand; M. Heran; G. Mannina; I. Rodriguez-Roda; I. Smets; A. Robles (Water Research, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Combining traditional and quantitative multiscale structural analysis to reconstruct the tectono-metamorphic evolution of migmatitic basements: the case of the Valpelline Series, Dent-Blanche Tectonic System, Western Alps - F. Caso; C.B. Piloni; M. Filippi; A. Pezzotta; E. Fazio; R. Visalli; G. Ortolano; M. Roda; M. Zucali (Journal of Structural Geology, 2024)

Pork carcass composition, meat and belly qualities as influenced by feed efficiency selection in replacement boars from Large White sire and dam lines - A. Saikia; G. Mejicanos; J. Rothy; E. Rajendiran; C. Yang; M. Nyachoti; H. Lei; R. Bergsma; Y. Wu; S. Jin; A. Rodas-Gonzalez (Meat Science, 2024)

Influence of corn supplementation to beef cows during mid- to late-gestation: Supplementation decreases placental microvascular surface density but does not alter uterine blood flow or neonatal performance1 - A.R. Tanner; M.L. Bauer; K.C. Swanson; V.C. Kennedy; J.D. Kirsch; J. Gaspers; N. Negrin-Pereira; A.B.P. Fontoura; G.A. Perry; G. Stokka; A. Rodas-Gonzalez; A. Ward; et al. (Livestock Science, 2023)

Carriage of ESBL-producing Enterobacterales in wastewater treatment plant workers and surrounding residents — the AWARE Study - Daloha Rodríguez-Molina; Fanny Berglund; Hetty Blaak; Carl-Fredrik Flach; Merel Kemper; Luminita Marutescu; Gratiela Pircalabioru Gradisteanu; Marcela Popa; Beate Spießberger; Tobias Weinmann; Laura Wengenroth; Mariana Carmen Chifiriuc; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
To investigate whether wastewater treatment plant (WWTP) workers and residents living in close proximity to a WWTP have elevated carriage rates of ESBL-producing Enterobacterales, as compared to the general population. From 2018 to 2020, we carried out a cross-sectional study in Germany, the Netherlands, and Romania among WWTP workers (N = 344), nearby residents (living ≤ 300 m away from WWTPs; N = 431) and distant residents (living ≥ 1000 m away = reference group; N = 1165). We collected information on potential confounders via questionnaire. Culture of participants’ stool samples was performed with ChromID®-ESBL agar plates and species identification with MALDI-TOF–MS. We used logistic regression to estimate the odds ratio (OR) for carrying ESBL-producing E. coli (ESBL-EC). Sensitivity analyses included stratification by country and interaction models using country as secondary exposure. Prevalence of ESBL-EC was 11% (workers), 29% (nearby residents), and 7% (distant residents), and higher in Romania (28%) than in Germany (7%) and the Netherlands (6%). Models stratified by country showed that within the Romanian population, WWTP workers are about twice as likely (aOR = 2.34, 95% CI: 1.22–4.50) and nearby residents about three times as likely (aOR = 3.17, 95% CI: 1.80–5.59) to be ESBL-EC carriers, when compared with distant residents. In stratified analyses by country, we found an increased risk for carriage of ESBL-EC in Romanian workers and nearby residents. This effect was higher for nearby residents than for workers, which suggests that, for nearby residents, factors other than the local WWTP could contribute to the increased carriage.

A morphological, reproductive, and molt phenology database for 379 bird species from the Colombian Tropical Andes - Leydy J. Cardona‐Salazar; Yeny A. Benavides‐Ossa; Ángela M. Vargas‐Daza; Juan F. Betancurt‐Grisales; Mauricio Bohada‐Murillo; Estefani T. Martínez‐Sánchez; Marelid Cardona‐Romero; Ana Busi; William D. Tobón‐Escobar; Mateo Ortíz‐Giraldo; Daniela Gómez Castillo; Johnathan Alvarez‐Londoño; et al. (Ecology, 2020)
The Colombian Tropical Andes are one of the regions with highest bird diversity on Earth. However, information on bird morphology, reproductive phenology, and molt is particularly scarce in this region. Also, this region is heavily impacted by deforestation, and it is vulnerable to climate change. Hence, providing baseline information on life history and morphological traits will be essential to support future research on functional diversity, climate change effects, conservation, evolution, and phenology. To fill this gap, we have compiled information on bird distribution, morphology, molt, and reproductive phenology at 52 localities of the Department of Caldas, covering an elevation range between 148 and 3845 m. This compilation comprises a wide range of habitats, including native forests, forestry plantations, croplands, and paramo. Our database presents information for 3,398 records belonging to 379 bird species (representing 23 orders, 53 families, and 258 genera). From those records, 2,843 correspond to information collected in the field between 2008 and 2019, and the remaining 555 records correspond to specimens deposited in the Natural History Museum of the Caldas University, collected between 1969 and 2014. We measured nine morphological traits from all specimens: total culmen, gape, bill width, bill depth, tarsus, wing length, tail length, total length, and mass. We also have reproductive condition information for 257 species and molt information available for 378 species. The information contained in this data set represents ~20% of the Colombian avifauna and ~11% of the bird species richness in South America. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Glucocerebrosidase expression patterns in the non-human primate brain - Iria G. Dopeso-Reyes; Diego Sucunza; Alberto J. Rico; Diego Pignataro; David Marín-Ramos; Elvira Roda; Ana I. Rodríguez-Pérez; José L. Labandeira-García; José L. Lanciego (Brain Structure and Function, 2018)

Neurochemical evidence supporting dopamine D1–D2 receptor heteromers in the striatum of the long-tailed macaque: changes following dopaminergic manipulation - Alberto J. Rico; Iria G. Dopeso-Reyes; Eva Martínez-Pinilla; Diego Sucunza; Diego Pignataro; Elvira Roda; David Marín-Ramos; José L. Labandeira-García; Susan R. George; Rafael Franco; José L. Lanciego (Brain Structure and Function, 2017)

The pandemic biotype of Austropuccinia psidii discovered in South America - G. M. Granados; A. R. McTaggart; I. Barnes; C. A. Rodas; J. Roux; M. J. Wingfield (Australasian Plant Pathology, 2017)

Detection of cannabinoid receptors CB1 and CB2 within basal ganglia output neurons in macaques: changes following experimental parkinsonism - Salvador Sierra; Natasha Luquin; Alberto J. Rico; Virginia Gómez-Bautista; Elvira Roda; Iria G. Dopeso-Reyes; Alfonso Vázquez; Eva Martínez-Pinilla; José L. Labandeira-García; Rafael Franco; José L. Lanciego (Brain Structure and Function, 2015)

Cannabinoid-free Cannabis sativa L. grown in the Po valley: evaluation of fatty acid profile, antioxidant capacity and metabolic content - G. Lesma; R. Consonni; V. Gambaro; C. Remuzzi; G. Roda; A. Silvani; V. Vece; G.L. Visconti (Natural Product Research, 2014)

Spatial distributions of the red palm mite, Raoiella indica (Acari: Tenuipalpidae) on coconut and their implications for development of efficient sampling plans - A. Roda; G. Nachman; F. Hosein; J. C. V. Rodrigues; J. E. Peña (Experimental and Applied Acarology, 2012)

Pathophysiology and therapeutic possibilities of calcitonin gene-related peptide in hypertension - I. Márquez-Rodas; F. Longo; R. P. Rothlin; G. Balfagón (Journal of Physiology and Biochemistry, 2006)

Leaf pubescence mediates the abundance of non-prey food and the density of the predatory mite Typhlodromus pyri - A. Roda; J. Nyrop; G. English-Loeb (Experimental and Applied Acarology, 2003)

Immnunohistochemical detection of phthalate esters in the alimentary canal of Tilapia spp. - G. Menghi; M. G. Sabbieti; M. Menghi; A. Roda; S. Materazzi; L. Marchetti (Journal of Fish Biology, 2002)
An examination of the occurrence and distribution of phthalate esters in the alimentary canal of a polyhybrid of Tilapia gave evidence of different and selective patterns of distribution in the organ tissues: the phthalate esters were shown to be concentrated in the stomach and anterior intestine. The restricted distribution of phthalate esters can have implications for the physiology of the digestive system. The phthalates, stored in the oxyntic cells of the gastric tubular glands, probably interfere with the digestive process. The strategic location of the enterocytes in the anterior intestine implies that they can hamper the reabsorption of digestion products. The endocrine disrupting effects known for these chemicals are probably related to the absorption of them via the alimentary canal.

Leaf pubescence and two-spotted spider mite webbing influence phytoseiid behavior and population density - A. Roda; J. Nyrop; G. English-Loeb; M. Dicke (Oecologia, 2001)

Trichomes and spider-mite webbing protect predatory mite eggs from intraguild predation - A. Roda; J. Nyrop; M. Dicke; G. English-Loeb (Oecologia, 2000)

Differences between lactate concentration of samples from ear lobe and the finger tip - J. Feliu; J. L. Ventura; R. Segura; G. Rodas; J. Riera; A. Estruch; A. Zamora; L. Capdevila (Journal of Physiology and Biochemistry, 1999)